Immunologic Strategies in Pancreatic Cancer: Making Cold Tumors Hot. Issue 24 (20th August 2022) - Ullman, Nicholas A.; Burchard, Paul R.; Dunne, Richard F.; Linehan, David C.
Abstract : The rising incidence and persistent dismal 5-year overall survival of pancreatic ductal adenocarcinoma (PDAC) highlight the need for new effective systemic therapies. Immunotherapy has shown significant benefits in solid organ tumors, but has thus far been disappointing in the treatment of PDAC. There have been several promising preclinical studies, but translation into the clinic has proved to be challenging. This is likely a result of PDAC's complex immunosuppressive tumor microenvironment that acts to insulate the tumor against an effective cytotoxic immune response. Here, we summarize the mechanisms of immunosuppression within the PDAC tumor microenvironment and provide an up-to-date review of completed and ongoing clinical trials using various immunotherapy strategies.